Notes on Prosthecarthron Raffray, with description of P. insulanus, sp. n. (Coleoptera, Staphylinidae, Pselaphinae) from Qi’ao Island, South China - Yin, Zi-Wei; Huang, Shao-Bin; Gu, Fu-Kang (Zootaxa, 2012)
The genus Prosthecarthron Raffray is redescribed. Prosthecarthron insulanus Yin & Huang, sp. n. is described from Qi’ao Island, South China and distinguished from the allied species. Illustrations of habitus and major diagnostic features of the new species are provided. An identification key, a distributional map and a list of species are included.